Applications of Big Data in Economic Information Analysis and Decision-Making under the Background of Wireless Communication Networks. (17th January 2022) - Deng, Yaotian; Zheng, Han; Yan, Jingshi
Abstract : Owing to the growing volumes of mobile telecommunications customers, Internet websites, and digital services, there are more and more big data styles and types around the world. With the help of big data technology with high semantic information, this paper focuses on exploring the value and corresponding application of big data in finance. By comparing with the existing methods in terms of search speed and data volume, we can effectively see the effectiveness and superiority of the algorithm proposed in this paper. Furthermore, the algorithm proposed in this paper can provide some reference ideas for the follow-up-related research work.